2020
DOI: 10.1097/rlu.0000000000003218
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Elastofibroma Dorsi With 68Ga-FAPI-46 and 18F-FDG PET/CT in a Patient With Esophageal Cancer

Abstract: A 71-year-old man underwent 18F-FDG and 68Ga-FAPI-46 PET/CT for initial staging prior to surgery of a squamous cell carcinoma of the lower esophagus under the prospective study NCT04147494. Both scans showed increased uptake in the mid and distal esophagus without evidence of metastatic disease. A soft tissue right infrascapular mass with mild 18F-FDG and moderate 68Ga-FAPI-46 uptake was incidentally found. The patient underwent robotic-assisted Ivor-Lewis esophagectomy and excision of the right infrascapular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In our study, 68 Ga-FAPI uptake of elastofibroma dorsi was higher in a patient than 18 F-FDG, consistent with the study by Hayrapetian et al 38 Similar to the study by Lan et al, 39 68 Ga-FAPI uptake was higher in the fracture observed in the rib in the same patient. In a case with focal 68 Ga-FAPI uptake in the pancreas, laboratory and radiological findings were evaluated in favor of pancreatitis, and 68 Ga-FAPI uptake due to pancreatitis has been reported in the literature 20,39 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 68 Ga-FAPI uptake of elastofibroma dorsi was higher in a patient than 18 F-FDG, consistent with the study by Hayrapetian et al 38 Similar to the study by Lan et al, 39 68 Ga-FAPI uptake was higher in the fracture observed in the rib in the same patient. In a case with focal 68 Ga-FAPI uptake in the pancreas, laboratory and radiological findings were evaluated in favor of pancreatitis, and 68 Ga-FAPI uptake due to pancreatitis has been reported in the literature 20,39 .…”
Section: Discussionsupporting
confidence: 92%
“…The blood perfusion status of the lesion can be directly evaluated based on the value of these perfusion parameters to reflect its development. At the same time, it can also judge the MVD and then evaluate the activity, pathological grade, and prognosis of the tumor (14). Tumor angiogenesis is the basic process of its growth and metastasis, and it is the physiological basis for tumor proliferation, nutrition supply, and metabolite elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Besides PSMA, there are multiple other targets discussed for their potency in PET/CT diagnostics or radioligand therapy. The fibroblast-activating protein (FAP) is used in 68Ga-Fibroblast activation protein inhibitor (FAPI) PET/CT [ 16 , 17 ] as well as 64Cu- and labelled with 225Ac FAPI combined in a “theranostics” approach [ 18 ].…”
Section: Introductionmentioning
confidence: 99%